1995
DOI: 10.3109/10929089509106335
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Surgical Arthroscopic Training

Abstract: Arthroscopy has become an irreplaceable method in diagnostics. The arthroscope, with optics and light source, and the exploratory probe are inserted into the knee joint through two small incisions underneath the patella. Currently, the skills required for arthroscopy are taught through hands-on clinical experience. Therefore, the Fraunhofer-Institut h e r Graphische Datenverarbeitung in Darmstadt, in cooperation with the Berufsgenossenschafiche Unfallklinik Frankfurt am Main, developed a highly interactive med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…There are also simulators that use virtual reality, in which the physician plans procedures using virtual human bodies, and human anatomy is studied threedimensionally and interactively. However, all of these have a high cost of use (19)(20)(21)(22) , thus limiting the accessibility of this training method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also simulators that use virtual reality, in which the physician plans procedures using virtual human bodies, and human anatomy is studied threedimensionally and interactively. However, all of these have a high cost of use (19)(20)(21)(22) , thus limiting the accessibility of this training method.…”
Section: Discussionmentioning
confidence: 99%
“…The sparseness of specific literature for the purposes of professional education and training creates difficulty in the training process for this very specific field (2) . Many methods are used for surgical training, and these may include using cadavers (15) , animals (16,17) and/ or synthetic models (15) , as well as training using virtual software (18)(19)(20)(21)(22) . The methods for learning to perform videoarthroscopy involve high costs, because high-technology equipment needs to be used, which is generally imported: the monitor, camera, light source and optics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some research projects have begun to test the feasibility of using VEs in medicine and E-health [19]. Applications of this technology are being developed for health care in the following areas: surgical procedures (remote surgery or telepresence [30][31][32], augmented or enhanced surgery [33][34], and planning and simulation procedures before surgery [35][36]); medical therapy [37][38][39][40][41][42][43][44][45]; neuro-psychology [46][47][48][49][50][51][52]; preventive medicine and patient education [Hoffman, 1995 #264; [53]]; medical education and training [54][55]; visualization of massive medical databases [56]; and skill enhancement and rehabilitation [57][58][59].…”
Section: Virtual Environmentsmentioning
confidence: 99%
“…This approach made it possible to use the psycho-physiological effects provoked by the virtual experience for therapeutical purposes.34-37 The developed module was tested in two different studies on nonclinical subjects:38 a first uncontrolled study on 72 male and female subjects35 and a second controlled study on 48 female subjects.37 The results of both studies showed that even a short-term application of the developed VE was able to modify the body experience disturbances of the subjects tested.38 VREPAR 2 Starting from the results described in the previous paragraph, the VREPAR 2 project is now testing the eating disorders (bulimia, anorexia, and obesity) module using clinical subjects. In particular, the project is trying to integrate the VR approach within the experimental-cognitive therapy (ECT), a relatively short-term, integrated, patient oriented approach that focuses on individual discovery.39 The treatment lasts approximately [9][10][11][12] weeks and it is administered by therapists having a cognitive-behavioral orientation who work in conjunction with a clinical psychologist as far as the pharmacological component is concerned.…”
Section: The Eating Disorders Modulementioning
confidence: 99%